PENGEMBANGAN PERANGKAT PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DALAM UPAYA MENUJU ERA INDUSTRI 4.0 - Ilham Rais Arvianto (De Fermat : Jurnal Pendidikan Matematika, 2019)
This research aims to develop high quality learning materials (RPS and RPP) in the event of the upcoming industrial era 4.0, from validity, practicality, and effectivity aspects to improve creative thinking ability. This development research consisted of 10 steps, i.e.: (1) research on previous research findings, (2) literary study, (3) designing and developing research instruments, (4) designing and developing products, (5) internal testing of the design, (6) design revision, (7) building research products, (8) limited testings, (9) product revision, and (10) public testings. This research was performed in STMIK Akakom Yogyakarta. The product of this research was regarded as of high quality if the criteria of validity, practicality, and effectivity are met. The data was collected using questionnaire (validity and practicality) and testing (effectivity). The result shows that in the event of the upcoming industrial era 4.0, the learning materials (RPS and RPP) are of hogh quality from validity, practicality, and effectivity aspects so as to be used to improve 31,7% creative thinking ability.